PENGARUH LATIHAN MULTIPLE BOX TO BOX JUMP WITH SINGLE LEG LANDING TERHADAP KECEPATAN TENDANGAN DEPAN - Nune Wire PanjiSakti; Muhammad Satria Mulyajaya (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
In extracurricular pencak silat of Tapak Suci SMAN 1 Gunungsari after observation, the researcher found that the low level of students' kick ability, found the kickback speed of martial arts athletes SMAN 1 Gunungsari very low, weak seen from the frequency of kicks done in every round average 3-5 times. Thus, the aspect of these skills becomes absolute controlled by the martial arts athletes in the process of coaching to a higher level can be sustainable. Relation with this on extracurricular pencak silat Tapak Suci SMAN 1 Gunungsari, that the low ability of students can be caused because the training method provided only limited to the improvement of basic motion techniques. The problem revealed from this research is "Is there any effect of multiple box to box jump exercise with single leg landing against front kick speed in extracurricular students martial arts pencak silat SMAN 1 Gunungsari 2017". The purpose of obtaining scientific information and want to know "Is there any effect of multiple box to box jump exercise with single leg landing against thespeed of front kick in the students extracurricular pencak silat tapak suci SMAN 1 Gunungsari 2017". The population in this research is the  extracurricular team of Pencak Silat SMAN 1 Gunungsari in 2017 which amounted to 20 people. Researchers used a flat field location to do front kick exercises and tests using sandsack, stationery and test stamps. The method used in this research is the action test method that is the test to do multiple box to box jump exercise with single leg landing for 6 weeks. Based on result of data analysis by using t-test formula hence can be got t-hitung (11.984) and t-table (1.729) at significant level 5% mean t-count bigger than t-table. Thus Hypothesis Nil (Ho) "Denied" and Alternative Hypothesis (Ha) "Accepted", so it can be concluded that "There is influence of multiple box to box exercise jump with single leg landing against front kick speed on students extracurricular pencak silat tapak suci SMAN 1 Gunungsari in 2017 ".